The potential of trans‐local policy networks for contributing to sustainable food systems—The Dutch City Deal: Food on the Urban Agenda. Issue 1 (31st May 2021) - Sibbing, Lara; Candel, Jeroen; Termeer, Katrien
Abstract: To foster more sustainable food systems, collaboration between local governments for knowledge exchange and cooperation is essential. Trans‐local food policy networks potentially serve this purpose but their functioning and outcomes remain largely unexplored. We address this gap by analyzing collaboration and its outcomes for one of the first trans‐local food policy networks in the Netherlands: City Deal: Food on the Urban Agenda. We use Ansell and Gash's collaborative governance model as an ideal type to analyze the City Deal drawing on two rounds of semi‐structured interviews with civil servants and politicians in 2016 and 2019 resulting in a total of 37 interviews with 49 unique respondents. The collaborative process was a continuous searching and negotiating for roles, goals, and activities, on the one hand, combined with great eagerness among participants to collaborate and improve local food systems on the other. Although this process led to collective identity building and learning, it resulted in limited collaborative action between participants or tangible results on the ground. The main outcomes were the active network itself, which fostered the strengthening of connections, exchanging knowledge, learning, and agenda setting. Based on our findings, we identify five key points of attention for successful food policy collaboration: ensuring stakeholder commitment, striking a balance between a sectoral and holistic focus, avoiding too abstract ambitions, fostering interdependence, and investing in political commitment. Core Ideas: Collaboration between local governments is key for effective local food policy The factors that constrain and stimulate trans‐local food policy collaboration are unknown Food policy collaboration is about identity building and learning not collective action Striking a balance between a sectoral and holistic focus proves key for collaboration Lack of shared understanding and political commitment can constrain collaboration